Data Analytics in the Utilization of ICT for Disaster Preparedness Plan of HEIs Region V - Arispe, Maria Charmy A.; Jr, Daniel E. Maligat,; Palaoag, Thelma D. (International Journal of Engineering and Technology, 2018)
This research paper provides an overview of Disaster Risk Management, its information and communication needs, and the applications of Information Communication Technology in its activities. It aimed to determine the utilization of ICT in Higher Education Institutions of Region V, Philippines through data analytics as basis for decision support for disaster preparedness planning. The results are summarized according to the number of respondents and type of disasters; data mining techniques for proper cooperation mechanisms with the usage of ICT; and the sentiment analysis to the current practices of HEIs in the utilization of ICT in disaster preparedness. By revealing the utilization of ICT for disaster preparedness in the higher education level, a collaborative solution as fundamental to the success of DRM was determined to help school communities better understand the current disaster situation and know how the community is recovering. Finally, a comprehensive disaster preparedness plan for HEIs of Region V in the utilization of ICT has been proposed to show that the potential impact of ICT for DRM policies and measures need to take into consideration on HEIs environment, and ensure that interventions do not increase student’s vulnerability to hazards.